Speak with butterflies a unique public speaking guidebook - De los Reyes, Rodolfo A. (PROSEC (Professional Skills Enrichment Center), 1993)
This book is an invaluable guide for everyone of us who has a message to convey and wants to convey it with effectiveness and conviction it is a book about public speaking, it contains tips on how to deliver what you want to say effectively. It also contains sample speeches.